Perbandingan Hasil Iklan Meta PT Kuliah Saham Indonesia Berdasarkan Tipe Konten dan Waktu Penerbitan: Comparative Analysis of Meta Advertising Results of PT Kuliah Saham Indonesia Based on Content Type and Publishing Time - Azzahra, Tiara; Munandar, Jono Mintarto (Jurnal Aplikasi Bisnis dan Manajemen, 2023)
PT Kuliah Saham Indonesia is an online educational content creator about investing and trading in the stock market as a solution to increase the knowledge of the millennial generation in the field of investment and stock trading. This research aimed to determine the characteristics of audiences on the advertising results of PT Kuliah Saham Indonesia, analyze the differences in advertising results based on the type of content and advertising publishing time used by PT Kuliah Saham Indonesia, describe alternatives to the best advertising strategy of PT Kuliah Saham Indonesia based on the type of content and time of advertising issuance. The analysis methods used are descriptive analysis, Two Way Anova analysis, and Simple Additive Weighting analysis. The sample used in this study was a meta advertisement of PT Kuliah Saham Indonesia in June 2022. The results showed that there were significant differences in ad content types, no significant differences in publishing time, and there were significant interactions with content types and publishing times. In addition, content type 3 with a value of 2.84 and nighttime publishing time with a value of 2.50 is the best advertising strategy at PT Kuliah Saham Indonesia. Keywords: content type, meta ads, two way anova, simple additive weighting, PT Kuliah Saham Indonesia